Policy Implications of Public Cemetery Management for Residents Security in Selected States in South-West, Nigeria - Adeforiti, Rotimi (Pascasarjana Universitas Mataram, 2025)
Despite the capability of public cemeteries to accommodate deviant behaviour, it has not formed an item of analysis in understanding insecurity in residential areas in South-West, Nigeria. The study identified the forms of security threats public cemeteries pose for residents in South-West, Nigeria; examined the management of public cemeteries in South-West, Nigeria; and reviewed residents’ roles in cemetery security in South-West, Nigeria. The study was guided by the assumption that a public cemetery is not a security threat to residents in Nigeria. The theoretical framework adopted and applied to the study is the Broken Windows Theory. The theory was adopted and applied to the study from the perspective that neighbourhood challenges are not promptly and properly addressed, such as the activities of deviant persons in cemeteries lead to more neighbourhood challenges. The study noted that public cemetery implies environmental abuse, security threats, physical abuse, and health challenges to residents. Public cemeteries are poorly managed, resulting from poor funding. Residents’ role in the protection of public cemeteries has been identified to include complaints and praise to the appropriate authority. Hence, the assumption of the study that a public cemetery is not a threat is valid because it is the management failure of the facility that informs the possible threat it poses to residents. The study recommended that prompt attention should be paid to the management of public cemeteries wherever located. Also, residents should be empowered to protect public cemeteries in their respective areas.